Understanding Gen Z’s Visit Intention to Sapa, Vietnam: An Integrated Motivation-TPB-Destination Image Approach - Setiyawan, Maria Gracetania Felly; Dharomesz, Vonezyo Yupanzara (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
This study examines Gen Z's intention to visit Sapa, Vietnam, focusing on the M-TPB-D framework and push and pull theory of motivation. Gen Z was chosen as the focus due to their growing impact on tourism behavior. A quantitative survey of 101 respondents using a purposive sampling technique was analysed using PLS-SEM. The finding reveals that Gen Z is attracted to destinations that offer uniqueness, are visually appealing, and support their value for personal experience. This study indicates the importance of integrating the value of Gen Z regarding destination image and their destination choice, which leads to visit intention to Sapa, Vietnam. It is concluded that Gen Z can be easily engaged through attractive destinations, personal-experience fulfillment, and digital influence, which shape their tourism behavior. However, this study may not be generalizable. Indeed, to attract tourists’ visit intention, some aspects should be incorporated into future studies to optimize outcomes.